2018
DOI: 10.1016/j.scog.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic signal for symptom dimensions and cognitive performance in patients with chronic schizophrenia

Abstract: Genetic etiology of psychopathology symptoms and cognitive performance in schizophrenia is supported by candidate gene and polygenic risk score (PRS) association studies. Such associations are reported to be dependent on several factors - sample characteristics, illness phase, illness severity etc. We aimed to examine if schizophrenia PRS predicted psychopathology symptoms and cognitive performance in patients with chronic schizophrenia. We also examined if schizophrenia associated autosomal loci were associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…A prior study in schizophrenia patients found that negative symptoms were significantly more severe in cases with a higher number of CNV‐disrupted genes ( n ≥ 13) than a fewer number of CNV‐disrupted genes ( n ≤ 6) (Lee, Liu, Wen, Chang, & Hwu, ). Recent studies have reported that polygenic risk scores can strongly predict symptom dimensions in schizophrenia, namely both positive and negative symptoms (Xavier et al, ), and only negative symptoms (Bigdeli et al, ), suggesting that many schizophrenia risk loci may influence dimensions of symptomatology and clinical presentations of schizophrenia. Higher levels of self‐disturbance were found in CHR‐P individuals compared to controls and predicted time to transition to psychosis (Nelson, Thompson, & Yung, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prior study in schizophrenia patients found that negative symptoms were significantly more severe in cases with a higher number of CNV‐disrupted genes ( n ≥ 13) than a fewer number of CNV‐disrupted genes ( n ≤ 6) (Lee, Liu, Wen, Chang, & Hwu, ). Recent studies have reported that polygenic risk scores can strongly predict symptom dimensions in schizophrenia, namely both positive and negative symptoms (Xavier et al, ), and only negative symptoms (Bigdeli et al, ), suggesting that many schizophrenia risk loci may influence dimensions of symptomatology and clinical presentations of schizophrenia. Higher levels of self‐disturbance were found in CHR‐P individuals compared to controls and predicted time to transition to psychosis (Nelson, Thompson, & Yung, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found significant associations between polygenic risk scores and symptom dimensions of schizophrenia (e.g., positive and negative symptoms, neurocognition) suggesting that many schizophrenia risk loci may influence the clinical presentation (Bigdeli et al, ; Xavier, Dungan, Keefe, & Vorderstrasse, ). A recent study supported the hypothesis that the common‐variant, genome‐wide association findings for schizophrenia point to a limited set of involved neurons, namely, medium spiny neurons, pyramidal neurons in hippocampal CA1, pyramidal neurons in the somatosensory cortex as well as cortical interneurons, and the gene sets also point to the same cells (Skene et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Significant associations between SZ-PRS and attention are only reported by Nakahara et al [27] , while other studies did not reveal any significant association between SZ-PRS and attention [28,33] . Post hoc analysis by Xavier et al [35] revealed a significant association between SZ-PRS and vigilance but the finding did not survive correction for multiple testing.…”
Section: Attention/vigilancementioning
confidence: 95%
“…Wang et al, 2018 [33] Schizophrenia Trio Genomic Research in Taiwan Whalley et al, 2016 [34] Generation Scotland:the Scottish Family Health Study: Xavier et al, 2018 [35] Clinical Antipsychotics Trials of Intervention Effectiveness-schizophrenia trial:…”
Section: Author and Year Sample Domain (Test) *Significantmentioning
confidence: 99%
“…These studies have been primarily conducted using candidate-gene approaches and small samples, and they have been criticized based on the minimal effect size of a single variant and their lack of statistical power. In view of polygenic profiles of neuroimaging and cognitive phenotypes [61,62], genomic data should be integrated to identify normal and abnormal gene-brain-behavior pathways. Since environmental factors alone and gene-environment interactions affect neuroimaging and cognitive phenotypes [6,63,64], it is important to identify the environmental factors associated with these phenotypes, which would help better guide clinical practice to address these adverse environmental factors.…”
Section: Gene (Environment)-brain-behavior Pathwaysmentioning
confidence: 99%